Comparison of upper extremity muscle activation levels between isometric and dynamic maximum voluntary contraction protocols - Warnock, B.; Gyemi, D. L.; Brydges, E.; Stefanczyk, J. M.; Kahelin, C.; Burkhart, T. A.; Andrews, D. M. (International Journal of Kinesiology & Sports Science, 2019)
Background: Muscle activations (MA) during maximum voluntary contractions (MVC) are commonly utilized to normalize muscle contributions. Isometric MVC protocols may not activate muscles to the same extent as during dynamic activities, such as falls on outstretched hands (FOOSH), that can occur during sport or recreational activities. Objective: The purpose of this study was to compare the peak MA of upper extremity muscles during isometric and dynamic MVC protocols. Methods: Twenty-four (12 M, 12 F) university-aged participants executed wrist and elbow flexion and extension actions during five-second MVC protocols targeting six upper extremity muscles (three flexors and three extensors). Each protocol [isometric (ISO); dynamic (eccentric (ECC), concentric (CON), elastic band (ELAS), un-resisted (UNRES)] consisted of three contractions (with one-minute rest periods between) during two sessions separated by one week. Muscle activation levels were collected using standard electromyography (EMG) preparations, electrode placements and equipment reported previously. Results: Overall, the ECC and CON dynamic protocols consistently elicited higher peak muscle activation levels than the ISO protocol for both males and females during both sessions. Over 95% of the CON trials resulted in mean and peak muscle activation ratios greater than ISO, with 56.3% being significantly greater than ISO (p < 0.05). Conclusion: Higher activation levels can be elicited in upper extremity muscles when resistance is applied dynamically through a full range of motion during MVC protocols.